Superstructure Fiber Gratings via Single Step Femtosecond Laser Inscription - Kalli, Kyriacos; Davies, Edward M.; Komodromos, Michael; Allsop, Thomas P.; Webb, David; Zhang, Lin; Koutsides, Charalambos (My University, 2012)
We present the development of superstructure fiber gratings (SFG) in Ge-doped, silica optical fiber using femtosecond laser inscription. We apply a simple but extremely effective single step process to inscribe low loss, sampled gratings with minor polarization dependence. The method results in a controlled modulated index change with complete suppression of mode coupling associated with the overlapping LPG structure leading to highly symmetric superstructure spectra, with the grating reflection well within the Fourier design limit. The devices are characterized and compared with numerical modeling by solving Maxwell's equations and calculating the back reflection spectrum using the bidirectional beam propagation method (BiBPM). Experimental results validate our numerical analysis, allowing for the estimation of inscription parameters such as the ac index modulation change, and the wavelength, position and relative strength of each significant resonance peak. We also present results on temperature and refractive index measurements showing potential for sensing applications.
Keywords: Femtosecond lasers; Numerical analysis; Maxwell equations; Optical fibers; Silica